An NAD+-dependent novel transcription factor controls stage conversion in Entamoeba - Dipak Manna; Christian Stephan Lentz; Gretchen Marie Ehrenkaufer; Susmitha Suresh; Amrita Bhat; Upinder Singh (eLife, 2018)
Developmental switching between life-cycle stages is a common feature among parasitic pathogens to facilitate disease transmission and pathogenesis. The protozoan parasite Entamoeba switches between invasive trophozoites and dormant cysts, but the encystation process remains poorly understood despite being central to amoebic biology. We identify a transcription factor, Encystation Regulatory Motif-Binding Protein (ERM-BP), that regulates encystation. Down-regulation of ERM-BP decreases encystation efficiency resulting in abnormal cysts with defective cyst walls. We demonstrate that direct binding of NAD+ to ERM-BP affects ERM-BP conformation and facilitates its binding to promoter DNA. Additionally, cellular NAD+ levels increase during encystation and exogenous NAD+ enhances encystation consistent with the role of carbon source depletion in triggering Entamoeba encystation. Furthermore, ERM-BP catalyzes conversion of nicotinamide to nicotinic acid, which might have second messenger effects on stage conversion. Our findings link the metabolic cofactors nicotinamide and NAD+ to transcriptional regulation via ERM-BP and provide the first mechanistic insights into Entamoeba encystation.